Development and Aging of the Kisspeptin–GPR54 System in the Mammalian Brain: What are the Impacts on Female Reproductive Function? - Franceschini, Isabelle; Desroziers, Elodie (Frontiers in Endocrinology, 2013)
The prominent role of the G protein coupled receptor GPR54 and its peptide ligand kisspeptin in the progression of puberty has been extensively documented in many mammalian species including humans. Kisspeptins are very potent GnRH secretagogues produced by two main populations of neurons located in two ventral forebrain regions, the preoptic area and the arcuate nucleus (ARC). Within the last two years a substantial amount of data has accumulated concerning the development of these neuronal populations and their timely regulation by central and peripheral factors during fetal, neonatal and peripubertal stages of development. This review focuses on the development of the Kisspeptin-GPR54 system in the brain of female mouse, rat, sheep, monkey and humans. The notion that this system represents a major target through which signals from the environment early in life can re-program reproductive function will also be discussed.